TEMPO-oxidised nanocellulose hydrogels and self-standing films derived from bacterial cellulose nanopaper - Yang,Y; Wloch,D; Lee,K-Y (RSC Advances: an international journal to further the chemical sciences, 2021)
Hydrogels derived from TEMPO-oxidised cellulose nanofibrils (TOCNs) are not robust and inherently water unstable if theTOCNs are not crosslinked or coated with a water-swellable polymer. Furthermore, the manufacturing of self-standing TOCNfilms is still a challenge due to the small TOCN diameter and viscosifying effect. Here, we report the TEMPO-mediatedoxidation of bacterial cellulose (BC) nanopaper as a route to produce robust and water stable TOCN hydrogel without theneed for additional additives or crosslinking steps, as well as self-standing TOCN films without the need for vacuum filtrationor slow-drying of TOCN suspension. Pristine BC pellicle was first press-dried into a dried and well-consolidated BC nanopaper,followed by TEMPO-oxidation at various NaClO concentrations. The oxidation reaction introduced carboxylate moieties ontoexposed BC nanofibrils within the nanopaper network structure. This then led to the swelling of the nanopaper into ahydrogel. A swelling ratio of up to 100 times the original thickness of BC nanopaper was observed upon TEMPO-oxidation.The water retention value of the TEMPO-oxidised BC hydrogels was also found to increase with increasing carboxylatecontent. These TEMPO-oxidised BC hydrogels were found to be robust and water-stable, even under prolonged (>1 month)magnetic stirring in water. We further showed that high grammage self-standing TOCN films (100 g m-2) can be fabricatedas simple as press-drying a water stable TEMPO-oxidised BC hydrogels without the need of vacuum-assisted filtration orslow-drying, which is typically the rate-limiting step in the manufacturing of self-standing TOCN films.